Vaginal myomectomy is superior to abdominal myomectomy in treatment effect and postoperative recovery - G.S. Wang; B. Wei (IMR Press, 2020)
Purpose: This study aimed to investigate the efficacy of vaginal myomectomy and abdominal myomectomy on cervical local microcirculation and ovarian function in patients harboring uterine fibroids during the perioperative period. Methods: From September 2017 to September 2019, 94 patients with uterine fibroids admitted in our hospital were randomly divided into the experimental group (vaginal myomectomy, N = 47) and the control group (abdominal myomectomy, N = 47). We compared vascular clarity, erythrocyte aggregation rate, microvascular diameter, blood perfusion, capillary diameter, E2, FSH, LH index and postoperative complications between the two groups. Results: On the 1 st and 3 rd day after operation, the vascular clarity, erythrocyte aggregation rate, microvascular diameter, blood perfusion and capillary diameter in the experimental group had superior beneficial effects compared with the control group, with significant difference (p < 0.05). One month and three months after operation, the E2 index of ovarian function in the experimental group was significantly higher than that in the control group (p < 0.05). However, the FSH and LH indexes in the experimental group were significantly lower than those in the control group (p < 0.05). The incidence of postoperative complications was significantly lower in the experimental group than that in the control group (p < 0.05). Conclusion: Vaginal myomectomy was the better surgical method for patients harboring uterine fibroids.